Faculty narcissism and student outcomes in business higher education: A student-faculty fit analysis. Issue 2 (July 2016) - Westerman, James W.; Whitaker, Brian G.; Bergman, Jacqueline Z.; Bergman, Shawn M.; Daly, Joseph P.
Abstract: We examined the relationship between personality congruence on faculty and student narcissism with student perceptions of professor status, the perceived difficulty of the class, and student performance in the classroom. Data were collected from business students and faculty at an AACSB-accredited business school at a comprehensive state university. Results indicated that narcissism congruence was significantly related to a student's final grade in the class such that less congruence was associated with lower course grades and that this negative association was partially mediated by perceived professor status and perceived class difficulty. Particularly concerning was the finding that more narcissistic faculty were associated with detrimental outcomes for less narcissistic students. Considering the well-documented and profoundly negative implications of narcissism for workplace environments, this finding suggests a need for future research on the impact of narcissistic faculty on business students and on successful intervention strategies. Highlights: Faculty-student personality congruence on narcissism was associated with enhanced undergraduate student grade performance. Faculty with higher levels of narcissism were associated with detrimental academic outcomes for less narcissistic students. Strategies for reducing faculty and student narcissism are suggested.